Peran deep learning dalam meningkatkan keterampilan pemecahan masalah siswa - Hayati, Rahmi (Karoteh Utama, 2025)
Problem-solving skills are essential 21st-century competencies that need to be developed from an early age. This study aims to analyze the role of Deep Learning technology in enhancing students' problem-solving skills through a qualitative approach. The research methods employed include observation, in-depth interviews, and document analysis involving students who engaged in Deep Learning-based learning systems. The findings indicate that the implementation of this technology positively contributes to students’ ability to identify problems, formulate solution strategies, and think flexibly compared to conventional methods. Furthermore, the Deep Learning system provides real-time feedback, adapts task difficulty to students' individual abilities, and increases their learning motivation. However, the implementation of this technology also faces challenges such as infrastructure limitations, teachers' readiness, and students' adaptation to AI-based systems. Therefore, this study recommends integrating AI technologies into the curriculum, providing teacher training, and developing more user-friendly systems. These findings contribute to the advancement of technology-based education and serve as a foundation for further research on optimizing AI in learning.